2008
DOI: 10.14198/jopha.2008.2.2.05
|View full text |Cite
|
Sign up to set email alerts
|

The influence of social presence on acceptance of a companion robot by older people

Abstract: Abstract-If robotic companions are to be used in the near future by aging adults, they have to be accepted by them. In the process of developing a methodology to measure, predict and explain acceptance of robotic companions, we researched the influence of social abilities, social presence and perceived enjoyment. After an experiment (n=30) that included collecting usage data and a second experiment (n=40) with a robot in a more and less sociable condition we were able to confirm the relevance of these concepts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(142 citation statements)
references
References 36 publications
8
132
0
2
Order By: Relevance
“…We hypothesize that also for our user group, a higher score on the construct of social presence will correlate with a higher score on conversational expressiveness. As in earlier research (Heerink et al 2008), we found a higher score on social presence to correlate with a higher score on acceptance (as indicated by the expressed intention to use the system), we suspect conversational expressiveness to correlate with intention to use.…”
Section: Robots In Eldercaresupporting
confidence: 83%
See 2 more Smart Citations
“…We hypothesize that also for our user group, a higher score on the construct of social presence will correlate with a higher score on conversational expressiveness. As in earlier research (Heerink et al 2008), we found a higher score on social presence to correlate with a higher score on acceptance (as indicated by the expressed intention to use the system), we suspect conversational expressiveness to correlate with intention to use.…”
Section: Robots In Eldercaresupporting
confidence: 83%
“…Furthermore, there are factors like enjoyment, perceived ease of use, perceived usefulness, attitude, and anxiety that influence acceptance (Venkatesh et al 2003;Heerink et al 2008), and future results could explore their relation with conversational expressiveness and social presence. This would not only provide a more complete picture of the relationship between conversational behavior in humanrobot interaction and acceptance, it would also tell us more about what enhances the sense of social presence for this particular user group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It might have an influence on task performance, where impoverished social presence undermines it [25]. If human players perceived artificial opponents as not socially present, their enjoyment would decrease while interacting with them [63]. Social presence was found to be important for understanding another agent's intentions [6].…”
Section: Social Interactionmentioning
confidence: 99%
“…The next paper by Heerink [20] also makes use of the iCat in a user study -this time in an application featuring older people as end-users. The idea that the older population might find great benefit in the future from social robots has great potential though its an area that also raises complex ethical issues [21].…”
Section: This Issue Contentmentioning
confidence: 99%